Impact of Surgical Wait Time on Survival in Patients With Upper Urinary Tract Urothelial Carcinoma With Hydronephrosis - Zhao, Fangzheng; Qi, Nienie; Zhang, Chu; Xue, Ning; Li, Shuaishuai; Zhou, Raorao; Chen, Zeyu; Yao, Ruiqin; Zhu, Haitao (Frontiers in Oncology, 2021)
Abstract Background and Objectives: Due to the inevitability of waiting time for surgery, this problem seems to have become more pronounced since the outbreak of COVID-19, and due to the high incidence of preoperative hydronephrosis in upper urinary tract urothelial carcinoma (UTUC) patients, it is particularly important to explore the impact of preoperative waiting time and hydronephrosis on upper urinary urothelial carcinoma. Methods: 316 patients with UTUC who underwent radical surgery at a high-volume center in China between January 2008 and December 2019 were included in this study. We retrospectively collected the clinicopathologic data from the medical records.Firstly, all patients were divided into short-wait (<30 days), intermediate-wait (31-90 days) and long-wait (>90 days) groups according to the surgical wait time. The clinicopathological characteristics of each group were evaluated and the survival was compared. For patients with hydronephrosis, we subsequently divided them into two groups: short-wait (≤60 days) and long-wait (>60 days) groups according to the surgical wait time. Univariate and multivariate COX regression analysis were performed to evaluate the prognostic risk factor for patients with hydronephrosis. Results: Of the 316 patients, 173 were classified into the short-wait group (54.7%), 69 into the intermediate-wait group (21.8%) and 74 into the long-wait group (23.5%). The 5-year overall survival (OS) of all patients was 54.3%. The 5-year OS of short-wait, intermediate-wait and long-wait groups were 56.4%, 59.3% and 35.1%, respectively (P=0.045). In the subgroup analysis, we divided 158 UTUC patients with hydronephrosis into short-wait group (≤60 days) and long-wait group (> 60 days).The 5-year OS of long-wait group was significantly lower than the OS of short-wait group (44.2% vs 55.1%, P =0.023). In multivariate Cox regression analysis of UTUC patients with hydronephrosis, surgical wait time, tumor grade, pathological T stage, and tumor size were independent risk factors for OS and CSS. Lymph node involvement was also a prognostic factor for CSS. Conclusion: For UTUC patients with hydronephrosis, the OS and CSS of patients with surgical wait time of more than 60 days were relatively shorted than those of patients with surgical wait time of less than 60 days.